2017
DOI: 10.1177/1541931213601974
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Continuous Driving-Related Feedback on Drivers’ Response to Automation Failures

Abstract: During prolonged periods of autonomous driving, drivers tend to shift their attention away from the driving task. As a result, they require more time to regain awareness of the driving situation and to react to it. This study examined the use of informative automation that during Level-3 autonomous driving provided drivers with continuous feedback regarding the vehicle’s actions and surroundings. It was hypothesized that the operation of informative automation will trigger drivers to allocate more attention to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
(19 reference statements)
2
14
0
Order By: Relevance
“…Put differently, the MRs effectively exploit the idea that automated driving can independently involve driver monitoring transitions and control transitions (Lu et al, 2016). Our results align with previous studies Cohen-Lazry et al, 2017;Dziennus et al, 2016;Yang et al, 2017;Helldin et al, 2013), which have shown that MRs and other types of uncertainty indicators stimulate driver to allocate attention to the road when encountering an unpredictable driving environment, in turn yielding improved responses in critical situations.…”
Section: Main Findingssupporting
confidence: 88%
See 2 more Smart Citations
“…Put differently, the MRs effectively exploit the idea that automated driving can independently involve driver monitoring transitions and control transitions (Lu et al, 2016). Our results align with previous studies Cohen-Lazry et al, 2017;Dziennus et al, 2016;Yang et al, 2017;Helldin et al, 2013), which have shown that MRs and other types of uncertainty indicators stimulate driver to allocate attention to the road when encountering an unpredictable driving environment, in turn yielding improved responses in critical situations.…”
Section: Main Findingssupporting
confidence: 88%
“…Compared to without such an uncertainty symbol, the participants intervened with a longer time to collision (TTC) in case of automation failure. Other examples are a LED bar on the instrument cluster indicating the momentary abilities of the automation (Helldin, Falkman, Riveiro, & Davidsson, 2013;Large et al, 2017), an ambient LED strip changing its colour or blinking patterns based on hazard uncertainty information Yang et al, 2017), a continuous verbal notification informing the driver about the state of the ego car and the behaviour of other road users (Cohen-Lazry, Borowsky, & Oron-Gilad, 2017), and a lane-line tracking confidence notification (Tijerina et al, 2017). The results of these studies showed that participants who were provided with the uncertainty indication were better prepared in critical situations (Dziennus et al, 2016;Helldin et al, 2013;Yang et al, 2017).…”
Section: Monitoring Requests and Uncertainty Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Driver distraction is a widespread, yet complex issue [2,29,30]. The diverting of attention from activities critical for safe driving has been proven to cause accidents and loss of life.…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier work has aimed to solve the problem by providing continuous information to the driver during automated driving [2,5,46]. However, continuous information mediation about, for example, ongoing traffic or the functionality of the automated driving system can be distracting or neglected.…”
Section: Introductionmentioning
confidence: 99%